Estudio de prefactibilidad para la instalación de una planta procesadora de puré de manzana (Malus domestica) con quinua (Chenopodium quinoa) para infantes en doypack - Chavez Arancibia, Martha Gabriela (2020)
This Project is about the research of the technical, economic, financial and social viability of a processing plant of an apple pure and quinoa in doypack for infants. The product to be studied will be 100 grams with a design suitable for marketing to infants between 2 to 12 years. The demand estimated for this project ranges from 843,386 units to 2021 to 1,039,742 units in 2025.After analyzing the most important location factors for this project, it was determined that the location for the plant would be in Lurin, Lima. When analyzing the limit sizes of the project, it was observed that the selection of the size would be determined by the market- size, that is, the demand, this is mostly due to the fact that the technology-size is relatively high, the point-size of balance is less than demand and productive resources are massively in our country. In the plant layout chapter, when analyzing using the Guerchet method, it was determined that the minimum plant size is 374 m2. Likewise, this chapter shows the general disposition of the productive and administrative areas, when using the relational analysis. In the chapter of investments and economic evaluation, it was determined that the total of initial investment is S /. 413,027.98; of which 30% will be provided by equity capital and 70% by loan from the financial institution that proposes the best terms. In this chapter, it was also determined that the best rate is that of GNB Peru with 24%. In addition, the economic and financial evaluation of the project has been calculated in a base of 5 years and with a COK of 19.75%. Likewise, a NPV of S /. 74,886.14 and an IRR of 34%.